Magnetic and epr studies of α-, β-, and γ-fe2wo6 phases at low temperatures - Guskos, N.; Sadlowski, L.; Typek, J.; V. Likodimos; Gamari-Seale, H.; Bojanowski, B.; Wabia, M.; Walczak, J.; Rychlowska-Himmel, I. (Journal of Solid State Chemistry, 1995)
The polymorphic modifications α-, β-, and γ-Fe2WO6 of the iron tungstate system were studied by means of magnetic susceptibility and EPR measurements at low temperatures. Both methods revealed a significant paramagnetic contribution, probably resulting from local distortions of the antiferromagnetic bulk structure induced by a disturbed cation ordering or the presence of Fe2+ ions. The magnetic susceptibility revealed a peak at ∼260 K for all samples which can be related with an AF phase transition. The EPR spectra comprised the contribution of various isolated paramagnetic iron centers, one arising from high-spin Fe3+ ions in rhombic crystal field symmetry with E/D ≈ 1/3 and D ≈ 0.22 cm-1, an anisotropic EPR signal consistent with an S = 3/2 ground state with large zero-field splitting, and a dominant component in the g ≈ 2 region presumably arising from an S = 1/2; spin state. The latter spectra were tentatively attributed to the formation of multi-iron clusters, one of them invoking the presence of Fe2+ ions as well. For the βFe2WO6 phase an additional EPR spectrum was observed, which probably results from high-spin Fe3+ ions in a weak crystal field. © 1995 Academic Press. All rights reserved.
cited By 11